Mongolia Quarterly Economic Update, April 2011 - World Bank (Washington, DC, 2017)
Mongolia's prospects in the medium term look excellent from a growth perspective as well as a fiscal management perspective. Staying the course in the medium term means implementing the landmark Fiscal Stability Law (FSL) passed last year, and adopting a supportive integrated budget law this spring session of parliament. The economy grew 6.1 percent year-on-year (yoy) in 2010, following a contraction of 1.3 percent in 2009. The last quarter of 2010 ended with a broad-based recovery, supported by transportation, construction and wholesale and retail trade. The latest survey conducted in informal labor markets in March 2011 revealed no changes in the total number of casual workers compared to December. Mongolia has promising growth prospects. It has the opportunity now to exercise prudent fiscal and macroeconomic policies so it can steer clear of the mistakes made by other resource rich economies and achieve its potential.